2004
DOI: 10.1167/iovs.04-0078
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation in theELOVL4Gene Causes Autosomal Dominant Stargardt-like Macular Dystrophy

Abstract: In a European family with adSTGD-like MD, a novel ELOVL4 mutation was found to underlie the disorder. Transfection studies indicated that, unlike wild-type ELOVL4, the mutant protein does not localize to the ER but rather appears to be sequestered elsewhere in an aggregated pattern in the cytoplasm. Further analysis of the function of normal and mutant ELOVL4 will provide insight into the mechanism of macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
62
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 14 publications
1
62
0
Order By: Relevance
“…Stargardt disease | condensing enzyme | photoreceptor degeneration T hree independent mutations in the last exon (exon 6) of the elongation of very-long-chain fatty acids-like 4 (ELOVL4) gene cause the pathogenesis of autosomal-dominant Stargardtlike juvenile macular dystrophy [Stargardt3 (STGD3)], resulting in loss of central vision with progressive degeneration of the macula and peripheral retina in humans (1)(2)(3)(4). A recent study reported severe skin and brain dysfunction in patients with homozygous mutations in ELOVL4 (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Stargardt disease | condensing enzyme | photoreceptor degeneration T hree independent mutations in the last exon (exon 6) of the elongation of very-long-chain fatty acids-like 4 (ELOVL4) gene cause the pathogenesis of autosomal-dominant Stargardtlike juvenile macular dystrophy [Stargardt3 (STGD3)], resulting in loss of central vision with progressive degeneration of the macula and peripheral retina in humans (1)(2)(3)(4). A recent study reported severe skin and brain dysfunction in patients with homozygous mutations in ELOVL4 (5).…”
mentioning
confidence: 99%
“…A recent study reported severe skin and brain dysfunction in patients with homozygous mutations in ELOVL4 (5). The resultant frameshift leads to premature termination of the encoded protein, loss of its C-terminal endoplasmic reticulum (ER) retention signal, and subsequent protein mislocalization and aggregation in cultured cells (4,(6)(7)(8). In 2008, ELOVL4 was shown to be involved in the elongation of C26 to C28 very-long-chain (VLC) fatty acids, saturated (FA) and polyunsaturated (PUFA) (9).…”
mentioning
confidence: 99%
“…Three alleles have been identified as the cause for STGD3, each possessing a mutation in the last exon (exon 6) of ELOVL4. These mutations include a 5-bp deletion (790 -794delAACTT), two 1-bp deletions (789delT and 794delT), and a single transversion (C-to-G at position 810) resulting in a premature stop codon (Y270X) (4,10,11). Each ELOVL4 mutation results in a truncated protein with a carboxyl-terminal dilysine motif absent, leading to loss of retention in the ER; very long chain polyunsaturated fatty acid (VLC-PUFA) biosynthesis takes place in the ER (12).…”
mentioning
confidence: 99%
“…Both the 5-bp deletion and the two 1-bp deletions are predicted to result in a similar truncated ELOVL4 protein. A third mutation in ELOVL4, 270stop, which should also generate a truncated ELOVL4 protein, has been identified recently in a Dutch family with dominant STGD (10). The importance of the function of ELOVL4 in the synthesis of polyunsaturated fatty acids is emphasized by the observation that the severity of STDG3 can be alleviated by dietary supplements of EPA and DHA (11,12).…”
mentioning
confidence: 99%